Modeling the dynamics of power circuits using a generalized state space model - Miraziz V. Sagatov; Oleksandr A. Sytnik (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: one of the pressing issues in the development of modern energy is the development of new models and the modernization of existing high-efficiency power plants. The evolution of modern power plants is characterized by a steady trend toward expanding their scope of application and increasing complexity. Power plants have evolved from systems with simple analog regulators to modern computer-controlled systems, which, as a result, offer new capabilities, including flexible control algorithms, remote control, and more. Requirements for the functionality and reliability of such plants have increased significantly, improving their dynamic characteristics, developing control and diagnostic subsystems, and expanding and complicating control functions using new intelligent technologies. One way to meet these requirements is the further development of methods and tools for mathematical and computer modeling of power plants themselves and their components, as well as their integration into design, control, monitoring, and diagnostic processes. Aim: analysis and justification of the use of a generalized state space model for modeling power circuits. Methods: of mathematical and computer modeling and elements of automatic control theory. Results: using a generalized state space model to simulate power circuit dynamics reduces the number of modeling equations and uses a single algorithm to solve a set of differential-algebraic equations. The results demonstrated the feasibility and effectiveness of this approach.